Introduction to Media Distribution : Film. Television. and New Media - KirkPtrick, Scott (new york : Routledge Taylor and Francis Group., 2023)
In this second edition, author Scott Kirkp.atrick draws from over a decade of p.ersonal exp.erience in the distribution arena to p.rovide a clear and up.-to-date overview of the entire film, television, and new media distribution business. Readers will learn what fuels the distribution p.rocess and exactly how the distribution business works from beginning to end$1 (Bnot merely what hap.p.ens to a film or television series up.on acquisition, but how distributors develop., p.resell and broker deals on content before it even exists. This new edition considers a much more international ap.p.roach to media distribution, with case studies and analyses from across the globe. It also reflects on the ever-increasing relevance of diversity and inclusiveness in the industry, as well as the new media verticals like p.odcasts and the effects of social media influencers on the media landscap.e. The book will be an integral guidebook for any student or p.rofessional wishing to understand both the basics and the subtleties of media distribution. The book also contains a robust ap.p.endix containing in-dep.th studies of legal definitions, material delivery requirements, territory-by-territory financial p.rojections and more.s
Keywords: New Media; Television; Film